THE MAXIM OF REQUESTING POLITENESS BETWEEN COLLEGE STUDENTS AND LECTURER (MAXIM KESANTUNAN DALAM TUTURAN PERMINTAAN ANTARA MAHASISWA DAN DOSEN) - Fhitri, Widya; Rahmayanti, Rahmayanti (Universitas PGRI Sumatera Barat, 2019)
This research is an advanced research from the previous research. This study aims at describing and explaining the politeness maxims that are fulfilled by the speech of student requesting to the lecturer at Dharma Andalas University. This research is a qualitative descriptive study. Data are obtained from the utterances of requesting spoken between students and lecturers. The theory used in data analysis is the maxim of politeness by Leech. Based on data analysis, it shows that the maxim of politeness that is often filled with student speech is the maxim of agreement. About 40 percent of the maxim of agreement is fulfilled by the speech of student requesting to the lecturers. On the otherhand,30 percent of maxim of symphaty occured in that anaysis. It was continued by the maxim of appreciation, the maxim of generosity and policy. However, the maxim of simplicity was not found in the speech of the student's requestingin Dharma Andalas University.